Effect of Yoga Program on Mental Health: Competitive Anxiety In Semarang Badminton Athletes - Kusuma, Donny Wira Yudha; Bin, Wang (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2017)
The most obvious factor which really affects the capability of an athlete, especially in Semarang badminton, is psychological factors. One technique supposed to represent all the mental techniques are yoga. A total of 20 athletes (12 men & 8 women) from the badminton club in Semarang participated in this study. Quasi-experimental was used in the study. Two groups were selected according age group and class, and both are candidates of the provincial team. We measured anxiety levels with CSAI-2R and sphygmomanometer. We analyze the data using t-test and index gain. Cognitive anxiety item on the yoga group decreased (x=-2.10; -21.21%), and so did the control group (x=-0.20; -2.19%). Somatic anxiety symptoms were similar to yoga group (x=-3.50; -26.92%), but not for the control group, which increased (x=1.70; 17.71%). Whereas self-confidence has a negative correlation to other variables, the yoga group increased (x=2.00; 12.35%) but the control group decreased (x=-0.30; -1.99%).The last was badminton performance, yoga group increased (x=2.40; 14.67%) and whereas the control group decreased (x=-3.283; -17.23%).